2014
DOI: 10.2320/matertrans.m2013301
|View full text |Cite
|
Sign up to set email alerts
|

Wear and Friction Properties of Mg–Zn–Y Alloy with Dispersion of Quasi-Crystalline Phase

Abstract: The wear and friction properties of the MgZnY alloys with a dispersion of the quasi-crystalline phase were investigated using the pin-ondisk configuration. The wear loss rates and the friction coefficient were obtained to be 1. /mm and 0.24 in the extruded alloy, respectively, under the dry wear condition. An effective method to enhance the wear properties in the magnesium alloys was determined to be a homogenous distribution of the quasi-crystalline phase in the coarse-grained matrix. Meanwhile, the grain ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For example, some dispersoids, such as fine ceramics and oxide particles, are usually introduced into microstructures intentionally to induce grain refinement and restrict grain growth. Recently, Somekawa et al [1] investigated the friction and wear properties of Mg-ZneY alloy with dispersion of quasi-crystalline phase. The corresponding experimental results indicated that the homogenous dispersive distribution of the quasi-crystalline phase in the coarse-grained matrix significantly enhances wear properties of the alloy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some dispersoids, such as fine ceramics and oxide particles, are usually introduced into microstructures intentionally to induce grain refinement and restrict grain growth. Recently, Somekawa et al [1] investigated the friction and wear properties of Mg-ZneY alloy with dispersion of quasi-crystalline phase. The corresponding experimental results indicated that the homogenous dispersive distribution of the quasi-crystalline phase in the coarse-grained matrix significantly enhances wear properties of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…However, Mg alloys usually exhibit poor wear resistance, which strongly limits their further applications at some extent. Thus, it is necessary to develop friction and wear properties of Mg alloys for the applications of many other parts such as the components around the engine parts [1].…”
Section: Introductionmentioning
confidence: 99%